2023
DOI: 10.1111/jocd.15700
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and efficacy assessment of an oral collagen supplement for the improvement of biophysical and ultrasonographic parameters of skin in middle eastern consumers

Abstract: Background Topical skin care products often do not reach the deeper layers of the skin, and oral hydrolyzed collagen is one of the newest and most popular systemic supplementations for skin rejuvenation. However, there are limited information in case of Middle Eastern consumers Objective The purpose of this study was to evaluate the tolerability and efficacy of an oral collagen supplement for improvement of skin elasticity, hydration, and roughness in Middle Eastern consumers. Methods and Materials It was a 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The question of these two anomalies is not explained and requires further follow‐up to call subjects for testing and conclusions. Some researchers have found that skin firmness is constant, independent of age 21 . R2, R5, and R7 did not show a purely linear relationship (Figure 1), but there was a significant moderate correlation with age (Figure 2).…”
Section: Discussionmentioning
confidence: 93%
“…The question of these two anomalies is not explained and requires further follow‐up to call subjects for testing and conclusions. Some researchers have found that skin firmness is constant, independent of age 21 . R2, R5, and R7 did not show a purely linear relationship (Figure 1), but there was a significant moderate correlation with age (Figure 2).…”
Section: Discussionmentioning
confidence: 93%
“…Also, as shown in figure 2 in Ref. 1 of the article, it seems that the questions were ratherleadinginnaturewhichcouldtipresponsestowardspossible exaggerationaswell.…”
Section: O R R E S P O N D E N C E Is Oral Collagen the Elixir Of Youth?mentioning
confidence: 97%
“…Dear Dr. Gold, Ihavereadthearticle"Tolerability and efficacy assessment of an oral collagen supplement for the improvement of biophysical and ultrasonographic parameters of skin in middle eastern consumers" 1 Finally, as shown by the figures in the study, participant satisfactionwasmeasuredatsetintervals,thatis,after6and12 weeks ofintake,aswellas4 weeksafterstoppingthetreatment(Week16) which raises the possibility of potential recall bias. Also, as shown in figure 2 in Ref.…”
Section: O R R E S P O N D E N C E Is Oral Collagen the Elixir Of Youth?mentioning
confidence: 99%
“…The variability of doses, age range, number of weeks tested, and skin measures does little to support the robustness of the clinical reports. However, there is a general pattern suggesting that HC is efficacious as an antiaging treatment for women who use the supplement for up to 12 weeks [ 15 , 16 ]. The conclusion of these systematic reviews and meta-analysis is that HC supplementation can improve skin hydration, elasticity, and wrinkles.…”
Section: Introductionmentioning
confidence: 99%